2014
DOI: 10.1136/neurintsurg-2014-011141
|View full text |Cite
|
Sign up to set email alerts
|

Emergency carotid artery stenting in patients with acute ischemic stroke due to occlusion or stenosis of the proximal internal carotid artery: a single-center experience

Abstract: eCAS in patients with AIS due to proximal ICA stenosis or occlusion appears to be a technically feasible and effective method for achieving good clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 28 publications
5
33
0
Order By: Relevance
“…This study showed a primary endpoint of recanalization without a sICH in 85% of patients (17/20). Our results were in accordance with results of previous similar studies (Table 3) 7, 8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25 . Furthermore, this study showed rates of recanalization, sICH, and mortality that were similar to those found in recent randomized trials on thrombectomy for acute stroke 2,3,4,5 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This study showed a primary endpoint of recanalization without a sICH in 85% of patients (17/20). Our results were in accordance with results of previous similar studies (Table 3) 7, 8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25 . Furthermore, this study showed rates of recanalization, sICH, and mortality that were similar to those found in recent randomized trials on thrombectomy for acute stroke 2,3,4,5 .…”
Section: Discussionsupporting
confidence: 83%
“…Carotid tandem occlusions are defined as both extra-cranial occlusion or stenosis of the internal carotid artery (ICA) and downstream intracranial vessel occlusion, which comprises a subgroup of patients that usually present poor recanalization rates under IVT and poor clinical outcomes 6 . Despite of the lack of clinical data from randomized trials on the best management course of acute carotid tandem occlusions, a combined recanalization strategy by means of carotid artery stenting and mechanical thrombectomy has recently shown promising results 7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25 . We aimed to assess the clinical and radiological data of patients who underwent carotid artery stenting (CAS) and endovascular treatment of acute ischemic stroke due to carotid tandem occlusions.…”
mentioning
confidence: 99%
“…However, the prognosis of patients with severe acute ischemic stroke (AIS) is unfavorable, 1) and rt-PA administration is usually ineffective. 1) Emergency PTA or CAS of the cervical ICA in the acute phase of AIS is indicated for Class IIb/Level of Evidence C patients according to the guidelines in 2013 published by the American Heart Association/American Scientific) was deployed and post-dilatation was performed using a Jackal RX 4 mm × 3 cm.…”
Section: Discussionmentioning
confidence: 99%
“…2,3) Recently, several studies have reported emergency CAS, but the incidence of postoperative intracranial hemorrhage was 0% to 39%. 1,[4][5][6] Few studies have compared the two procedures, and the results are inconsistent. 3,7) Choudhri et al 7) reported that the prognosis in the PTA group was more favorable than in the CAS group (incidence of postoperative intracranial hemorrhage: 35%, mortality rate: 29%).…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation